Preservation, Restoration and Upgrade of the Indian Institute of Management in Ahmedabad, India - Somaya, Brinda (Docomomo Journal, 2018)
Indian Institute of Management in Ahmedabad (IIMA), is under an ongoing conservation project to preserve, restore and upgrade the built fabric of the iconic and modern heritage structures designed by Louis I. Kahn, in India. These include eighteen dormitory buildings and the main complex (the school) housing four faculty blocks, the classroom complex and the Vikram Sarabhai library building. The project entails carrying out a detailed study of the cultural significance of the buildings, conducting surveys for preparation of as-built drawings, building condition mapping and assessment, preparation and execution of a detailed conservation plan and strategies for restoration, retrofitting and upgrading the built fabric along with its spatial expression, with due consideration to both its status as a significant work of 20th century monumental architecture and as a premier management institute of the country.